Jehovah's Witnesses and Their Compliance with Regulations on Smoking and Blood Treatment - Pavlikova, Barbara; van Dijk, Jitse P (International journal of environmental research and public health, 2021)
Jehovah's Witnesses (JWs) are known as a religious group compliant with the national laws in the case of smoking, but not-compliant when it comes to blood treatment. Their beliefs prevent them from taking part in a blood transfusion, which is widely included in standard methods of a life-saving treatment. The aim of this study was to compare the behavior of JWs regarding their approach to blood treatment and to smoking in relation to legal regulations in the field of health. We measured JWs' compliance with health laws regarding blood treatment and smoking (the Framework Convention on Tobacco Control-FCTC). We used the concept of a semi-autonomous social field by Moore and the theory of planned behavior developed by Ajzen. Our findings show that in the case of JWs, the group rules often prevail over state rules contained in generally-binding legislation. In the case of smoking, this means that they seem compliant to the FCTC and to their group rules. In the case of blood treatment, it seems that they are breaking the national rules, because of their group rules. Breaking the latter can result in exclusion from the JWs community. JWs are compliant with national laws as long as these are congruent with their own group rules. If this is not the case, the group influence is very strong and the fear of exclusion from the JW group is often greater than the potential negative health consequences in real life.
Keywords: Religion and Medicine; blood; náboženství a lékařství; kouření; Jehovah's Witnesses; compliance; křesťanství; Smoking; health laws; lidé; smoking; Svědkové Jehovovi; Treatment Refusal; odmítnutí terapie pacientem; Christianity; Jehovah’s Witnesses; Humans